Applications of mathematical modeling, machine learning, and intelligent computing for industrial development - Jain, Madhu, 1959-; Sharma, D. K. (Dinesh K.); Kulshrestha, Rakhee; Hota, H. S. (Smart technologies for engineers and scientists, 2023)
"The text presents emerging real-life topics on mathematical models, machine learning, and intelligent computing in a single volume. It will serve as an ideal text for senior undergraduate, graduate students, and researchers in diverse fields domains including industrial and manufacturing engineering, computer engineering, and mathematics"--